The FLUKA code: Overview and new developments - Ballarini Francesca; Batkov Konstantin; Battistoni Giuseppe; Bisogni Maria Giuseppina; Böhlen Till T.; Campanella Mauro; Carante Mario P.; Chen Daiyuan; De Gregorio Angelica; Degtiarenko Pavel V.; De la Torre Luque Pedro; dos Santos Augusto Ricardo; et al. (EPJ Nuclear Sciences & Technologies)
The FLUKA Monte Carlo Radiation Transport and Interaction code package is widely used to simulate the interaction of particles with matter in a variety of fields, including high energy physics, space radiation, medical applications, radiation protection and shielding assessments, accelerator studies, astrophysical studies and well logging. This paper gives a brief overview of the FLUKA program and describes recent developments, in particular, improvements in the modelling of particle interactions and transport are described in detail. In addition, an overview of selected applications is given.